Simulation of Land Use and Land Cover of Peatland Bengkalis Using QGIS - Fauziah, Fauziah; Hayati, Nur; Prasetyo, Lilik Budi (JOIV : International Journal on Informatics Visualization, 2025)
The phenomenon of forest and peatland fires in Bengkalis Regency is inseparable from the change in land use and cover (LULC). The dynamic LULC in Bengkalis Regency is caused by economic factors sourced from land-based resource management. As a result, negative impacts such as environmental damage can trigger fires. Therefore, this study attempts to observe the LULC patterns on peatlands in the Bengkalis Regency using overlay techniques using QGIS. QGIS functions unlock the software's full potential, empowering you to manipulate data, automate workflows, create custom expressions, and perform advanced spatial analysis—all within a single platform. There are 12 LULC that can be identified on peatlands in Bengkalis Regency, including plantations (42.98%), primary forests (42.68%), shrubs (12.29%), residential and activity areas (0.71%), fields/farmlands (0.64%), lakes/ponds (0.43%), empty/bare land (0.18%), rivers (0.05%), and ponds, ponds, mangrove forests, and rice fields ranging from 0.004% to 0.008%. In addition, in the Bengkalis Regency, concession areas of at least 175,081.19 Ha are in the Peatland Ecosystem Protection Function (FLEG). LULC simulation provides a powerful tool for assessing the potential impact of various development plans and policies on society, the economy, and the environment, enabling more sustainable and responsible choices. A comprehensive understanding of land use and land-cover patterns is essential for further research on sustainable resource management and climate change mitigation. While LULC research has advanced significantly, several critical questions require further investigation